Megkeresztelt gazdaság: a középkori angol céhek vallási aspektusai - Cseri, Máté (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
This paper focuses on medieval English guilds, especially craft guilds. Christianity was the unquestionable spiritual force behind the results of the Middle Ages – and talking about these scientific, cultural, religious achievements one cannot omit the role of guilds. Besides their significant economic activities, their main goal was the salvation of souls and to avoid purgatory.